Inventing Our University: Student-Faculty Collaboration in Critical University Studies - Steffen, Heather (Radical Teacher, 2017)
In this article, Heather Steffen reflects on her recent participation in a student-faculty collaborative research project, All Worked Up: A Project about Student Labor, and her experience teaching critical university studies. She considers the questions: What does critical university studies offer to students? What can students contribute to critical university studies? And how might such exchanges lead us beyond scholarship, enable us to build solidarity, and empower us to invent a new university, our university, that serves students, scholar-teachers, and its diverse publics rather than the imperatives of neoliberal capital? Because critical university studies has both scholarly and social justice goals, Steffen argues, we must continually look for ways to connect our research and writing to collective action. Research collaborations involving students, faculty, staff, and community members are not only important sites for learning and teaching, but also for creating the personal relationships, networks, knowledge base, and skills required to build solidarity and enact change in higher education.